The Mine-o-saur - Bardhan-Quallen, Sudipta; Clark, David, 1960 March 19- (New York, NY : G. P. Putnam's Sons, 2007)
The greedy Mino-o-saur learns the hard way that he needs to share the toys in order to make friends.
AD 400
Accelerated Reader AR
Keywords: Dinosaurs -- Fiction; Sharing -- Fiction; Toys -- Fiction; Friendship -- Fiction; Dinosaurs -- Juvenile fiction; Sharing -- Juvenile fiction; Toys -- Juvenile fiction; Friendship -- Juvenile fiction